Socket Shield Technique for Immediate Implant Placement in the Esthetic Zone: A Case Report - Pahari, S; Joshi, SP; Shrestha, P; Sah, S; Verma, A (Journal of Nepalese Prosthodontic Society, 2022)
The placement of implant following removal of compromised tooth is a common practice. Hard and soft tissue changes following tooth extraction, particularly on the labial aspect are known to occur. These changes compromise aesthetics, particularly in anterior maxilla leading to esthetic failure. Socket shield technique is known to prevent resorption of buccal bone, maintaining contour of buccal mucosa and achieving better result aesthetically. The purpose of this case report is to demonstrate the socket shield technique for immediate implant placement in anterior maxilla and restoration with cement retained prosthesis.